2021
DOI: 10.1002/hep4.1696
|View full text |Cite
|
Sign up to set email alerts
|

Ipragliflozin Improves the Hepatic Outcomes of Patients With Diabetes with NAFLD

Abstract: Sodium glucose cotransporter-2 inhibitors (SGLT2is) are now widely used to treat diabetes, but their effects on nonalcoholic fatty liver disease (NAFLD) remain to be determined. We aimed to evaluate the effects of SGLT2is on the pathogenesis of NAFLD. A multicenter, randomized, controlled trial was conducted in patients with type 2 diabetes with NAFLD. The changes in glycemic control, obesity, and liver pathology were compared between participants taking ipragliflozin (50 mg/day for 72 weeks; IPR group) and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 53 publications
5
62
1
Order By: Relevance
“…90 More recently, Takahashi et al conducted an open-label randomized controlled trial that aimed to examine the effect of ipragliflozin on hepatic pathology in 50 patients with T2DM and biopsyproven NAFLD. 91 These authors reported that patients treated with ipragliflozin (50 mg daily, n=24) for 72 weeks had better hepatic histology outcomes, including the severity of liver fibrosis and ballooning, compared to patients (n=26) who performed lifestyle modifications and/or took glucose-lowering drugs, with the exception of SGLT2 inhibitors, pioglitazone, or GLP-1RAs. 91 To date, however, no robust data from sufficiently large randomized controlled trials with liver histological endpoints are available to comment on the long-term efficacy of SGLT2 inhibitors as a treatment for NASH.…”
Section: Sodium-glucose Cotransporter-2 Inhibitorsmentioning
confidence: 99%
“…90 More recently, Takahashi et al conducted an open-label randomized controlled trial that aimed to examine the effect of ipragliflozin on hepatic pathology in 50 patients with T2DM and biopsyproven NAFLD. 91 These authors reported that patients treated with ipragliflozin (50 mg daily, n=24) for 72 weeks had better hepatic histology outcomes, including the severity of liver fibrosis and ballooning, compared to patients (n=26) who performed lifestyle modifications and/or took glucose-lowering drugs, with the exception of SGLT2 inhibitors, pioglitazone, or GLP-1RAs. 91 To date, however, no robust data from sufficiently large randomized controlled trials with liver histological endpoints are available to comment on the long-term efficacy of SGLT2 inhibitors as a treatment for NASH.…”
Section: Sodium-glucose Cotransporter-2 Inhibitorsmentioning
confidence: 99%
“…A number of clinical studies have highlighted the benefit of SGLT-2i in patients with T2DM and NAFLD ( Table 5 ) [ 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 ]. In the majority of them, the administration of SGLT-2i has resulted in improvement of serum levels of liver enzymes and hepatic steatosis, as evaluated by magnetic resonance imaging (MRI), ultrasound (U/S), non-invasive biomarkers, such as AST to platelet ratio (APRI) index, NAFLD fibrosis score (NFS) and Fibrosis-4 (FIB-4) score, or even by liver biopsy (LB).…”
Section: Sglt-2 Inhibitors In Nafldmentioning
confidence: 99%
“…In the majority of them, the administration of SGLT-2i has resulted in improvement of serum levels of liver enzymes and hepatic steatosis, as evaluated by magnetic resonance imaging (MRI), ultrasound (U/S), non-invasive biomarkers, such as AST to platelet ratio (APRI) index, NAFLD fibrosis score (NFS) and Fibrosis-4 (FIB-4) score, or even by liver biopsy (LB). In some of these studies, improvement in hepatic fibrosis was found, using transient elastography (TE) or LB, even though this finding was not univocal [ 146 , 153 , 158 , 159 , 164 , 165 , 168 ].…”
Section: Sglt-2 Inhibitors In Nafldmentioning
confidence: 99%
“…Ipragliflozin (50 mg/d for 72 weeks) ameliorated liver fibrosis and enhanced NASH resolution [ 154 ], remogliflozin etabonate (50–1000 mg/d for 12 weeks) reduced FIB-4 and NAFLD-fibrosis scores [ 155 ], and ertugliflozin (5 or 15 mg/d for 52 weeks) reduced liver transaminase levels [ 156 ] in TD2M patients with different stages of NASH. Several pilot studies in T2DM/NAFLD subjects confirmed the antisteatotic properties of luseogliflozin and tofogliflozin [ 157 , 158 , 159 ].…”
Section: Glucose Metabolism Modulatorsmentioning
confidence: 99%